Structural basis for noradrenergic regulation of neural circuits in the mouse olfactory bulb. Issue 9 (27th December 2020) - Horie, Sawa; Kiyokage, Emi; Hayashi, Shuichi; Inoue, Kanako; Sohn, Jaerin; Hioki, Hiroyuki; Furuta, Takahiro; Toida, Kazunori
Abstract: Olfactory input is processed in the glomerulus of the main olfactory bulb (OB) and relayed to higher centers in the brain by projection neurons. Conversely, centrifugal inputs from other brain regions project to the OB. We have previously analyzed centrifugal inputs into the OB from several brain regions using single‐neuron labeling. In this study, we analyzed the centrifugal noradrenergic (NA) fibers derived from the locus coeruleus (LC), because their projection pathways and synaptic connections in the OB have not been clarified in detail. We analyzed the NA centrifugal projections by single‐neuron labeling and immunoelectron microscopy. Individual NA neurons labeled by viral infection were three‐dimensionally traced using Neurolucida software to visualize the projection pathway from the LC to the OB. Also, centrifugal NA fibers were visualized using an antibody for noradrenaline transporter (NET). NET immunoreactive (‐ir) fibers contained many varicosities and synaptic vesicles. Furthermore, electron tomography demonstrated that NET‐ir fibers formed asymmetrical synapses of varied morphology. Although these synapses were present at varicosities, the density of synapses was relatively low throughout the OB. The maximal density of synapses was found in the external plexiform layer; about 17% of all observed varicosities contained synapses. These results strongly suggest that NA‐containing fibers in the OB release NA from both varicosities and synapses to influence the activities of OB neurons. The present study provides a morphological basis for olfactory modulation by centrifugal NA fibers derived from the LC. Abstract : We accomplished visualization and reconstruction of noradrenergic neurons projecting to the olfactory bulb (OB) by infection of adeno‐associated viruses into the locus coeruleus of dopamine beta hydroxylase‐Cre mice. An individual noradrenergic axon traveled while forming several branches and was distributed in multiple glomeruli that were located in different areas of the glomerular layer in the OB.